2023
DOI: 10.1097/jnn.0000000000000698
|View full text |Cite
|
Sign up to set email alerts
|

An International Study on Violence and Aggression in Neuroscience Nursing

Abstract: INTRODUCTION:The primary rationale for this study was to evaluate neuroscience registered nurses' (RNs') experience of violence and aggression internationally. The objectives were to determine how prevalent violence and aggression is in neuroscience nursing and the support and education provided. METHODS: Two online surveys were developed for neuroscience RN educators and RNs through SurveyMonkey. The questionnaires were distributed through RN organizations internationally in 2021. RESULTS: Two hundred seventy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Higher frequencies of violent incidents have continually been linked to reduced quality of patient care and decreased quality of life for healthcare employees [2]. Despite the prevalence and impact of WPV, studies have found that a signi cant number of organizational interventions fail to produce sustained improvements [7,8].…”
Section: Rationalementioning
confidence: 99%
“…Higher frequencies of violent incidents have continually been linked to reduced quality of patient care and decreased quality of life for healthcare employees [2]. Despite the prevalence and impact of WPV, studies have found that a signi cant number of organizational interventions fail to produce sustained improvements [7,8].…”
Section: Rationalementioning
confidence: 99%